Pendekatan management conflict untuk perubahan dan pengembangan organisasi - Malikul Adil (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Every manager these days face multifarious kinds of conflict problem, in their organization, In general people of opinion that that conflict always generate negative impact. Though, certain in a condition exactly conflict need for the take of change and development of organization. Beside conflict, every manager face also the problem of change that happened or which need initiation in theirorganization, so that the organization ever can accomodate with their environment, which by taking place time and also take to change. Development Problem also represent one of problem which must be solved by manager, because not only organizations have to be developed, but also human being in the organization require to also involve in development of organization, in order to effort face rival and environmental demand. Conflict - change - and development its intention of development of organization or development of organization in its word meaning other interconnected one another. Despitefully factors obliging the existence of change and also development of organization, also known and comprehended by contemporary manager, because development and also change represent a cycle 0f inheren of organization. Studying change conflict management - development, obliging us to also to comprehend psychological aspects, and aspects of sosiologis, beside economic aspects related to him.